Advances in CAR T cell therapy: antigen selection, modifications, and current trials for solid tumors - Khan, Safwaan H.; Choi, Yeonjoo; Veena, Mysore; Lee, John K.; Shin, Daniel Sanghoon (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR) T cell therapy has revolutionized the treatment of hematologic malignancies, achieving remarkable clinical success with FDA-approved therapies targeting CD19 and BCMA. However, the extension of these successes to solid tumors remains limited due to several intrinsic challenges, including antigen heterogeneity and immunosuppressive tumor microenvironments. In this review, we provide a comprehensive overview of recent advances in CAR T cell therapy aimed at overcoming these obstacles. We discuss the importance of antigen identification by emphasizing the identification of tumor-specific and tumor-associated antigens and the development of CAR T therapies targeting these antigens. Furthermore, we highlight key structural innovations, including cytokine-armored CARs, protease-regulated CARs, and CARs engineered with chemokine receptors, to enhance tumor infiltration and activity within the immunosuppressive microenvironment. Additionally, novel manufacturing approaches, such as the Sleeping Beauty transposon system, mRNA-based CAR transfection, and in vivo CAR T cell production, are discussed as scalable solution to improve the accessibility of CAR T cell therapies. Finally, we address critical therapeutic limitations, including cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), and suboptimal persistence of CAR T cells. An examination of emerging strategies for countering these limitations reveals that CRISPR-Cas9-mediated genetic modifications and combination therapies utilizing checkpoint inhibitors can improve CAR T cell functionality and durability. By integrating insights from preclinical models, clinical trials, and innovative engineering approaches, this review addresses advances in CAR T cell therapies and their performance in solid tumors.